Algorithmic versus teacher‐led sequencing in a digital serious game and the development of second language reading fluency and accuracy. (10th June 2021) - Serra, Judit; Gilabert, Roger
Abstract: Recent years have seen a surge of calls for personalization of education. Automatised adaptivity in serious games has been advocated as a potential instantiation of such calls. Yet little is known about the extent to which personalised learning through automatised adaptivity poses an advantage for language learning over generalised teacher‐led sequencing in digital, game‐based learning environments. The goal of this paper is to address this question by comparing the learning outcomes in reading accuracy and fluency of didactic sequences designed by EFL teachers or by an adaptive algorithm. A total of 67 participants completed several proficiency and reading skills pretest and posttest and used the iRead system for 6 months. Results showed that all learners made progress in reading skills, but no significant differences were found between the two sequences in relation to the development of reading skills. It was also shown that adaptivity works best if it leads to increase in the number of games per feature. Results are discussed in the context of previous findings, and the role of adaptivity and sequencing is critically assessed. Practitioner notes What is already known about this topic? Serious games have the potential to aid learning but empirical research is needed. Findings about the efficiency of serious games are mixed. Current and reviewed versions of the Simple View of Reading constitute a suitable framework to measure reading acquisition. What this paper adds? It contributes to the growing corpus of research on digital serious games. It provides empirical evidence on the use of an adaptive system in formal education. Comparing a teacher‐led sequence to an algorithmic adaptive sequence on the same digital serious game has never been done before. The paper shows the need to obtain both system‐internal and system‐external data in order to capture the impact of gameplay on the development of L2 reading skills. Implications for practise and/or policy It sheds some light on how certain game designs may actually help practise with different degrees of intervention by teachers. It is interesting for teachers to use an adaptive sequence that they can check and intervene in if needed.